Service Quality, Customer Experience and E-WOM on Customer Loyalty with Customer Satisfaction as the Mediating Factor in Online Travel Agent - A.A. Ayu Widiantari; Elvira Diva Shafa Ismananti; Ni Made Dwita Oktaviani; Ario S. Setiadi (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The burgeoning online travel agency (OTA) market in Indonesia has made building customer loyalty a top priority amid intensifying market competition. Existing literature typically examines service quality, customer experience, and electronic word of mouth (E-WOM) as independent factors, despite their recognized influence on consumer behavior. Objective: This study addresses this gap by testing an integrated model in which service quality, customer experience, and E-WOM influence customer loyalty through the mediating role of customer satisfaction. Methods: Using purposive sampling within a cross-sectional research design, this study collected responses from 409 OTA users aged 18–45 in Bali, Bandung, and Greater Jakarta. The data were analyzed using SmartPLS 4 and partial least squares structural equation modeling (PLS-SEM) to evaluate the proposed research model. Results: The findings indicate that service quality (β = 0.353, p < 0.001), customer experience (β = 0.244, p < 0.001), and E-WOM (β = 0.140, p = 0.006) significantly predict customer loyalty, with service quality emerging as the strongest predictor. Reciprocal relationships were identified between service quality and customer experience (β = 0.738) and between customer experience and E-WOM (β = 0.712). Customer satisfaction partially mediates the relationships between the predictor variables and customer loyalty. The model explains 57.1% of the variance in customer loyalty (R² = 0.571), while Q² values greater than zero for all endogenous constructs demonstrate the model’s predictive relevance. Conclusion: This study clarifies the integrated process through which customer loyalty develops in the online travel agency industry. It also provides actionable insights for practitioners seeking to strengthen customer retention by maintaining high service standards, creating meaningful customer experiences, and promoting active digital engagement. Theoretically, the study contributes an integrated cross-sectional PLS-SEM model that combines reciprocal path relationships with mediation analysis. Practically, OTA managers should prioritize service reliability and responsiveness as key drivers of customer loyalty. Nevertheless, the cross-sectional design represents an important limitation because it does not permit definitive causal inferences.